2011
DOI: 10.1111/j.1750-2659.2011.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐ and T‐cell memory elicited by a seasonal live attenuated reassortant influenza vaccine: assessment of local antibody avidity and virus‐specific memory T‐cells using trogocytosis‐based method

Abstract: Please cite this paper as: Petukhova et al. (2011) B‐ and T‐cell memory elicited by a seasonal live attenuated reassortant influenza vaccine: assessment of local antibody avidity and virus‐specific memory T‐cells using trogocytosis‐based method. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2011.00279.x. Purpose  The main purpose of vaccination is to generate immunological memory providing enhanced immune responses against infectious pathogens. The standard and most commonly used assay for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Furthermore, the antigenic distance we used is based on the serum hemagglutination inhibition (HI) assay. This has been historically used to measure the immune response to IIV, but there is increasing evidence that other assays measuring mucosal humoral responses might be better indicators of the LAIV immunogeniticy [61][62][63][64]. As more data becomes available on the antibody responses to different epitopes on the hemagglutinin and other proteins of influenza it may be possible to develop strategies that focus on the generation of responses to conserved eptiopes such as those on the stem of hemagglutinin and thus generate a universal influenza vaccine which avoids problems associated with strain variation [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the antigenic distance we used is based on the serum hemagglutination inhibition (HI) assay. This has been historically used to measure the immune response to IIV, but there is increasing evidence that other assays measuring mucosal humoral responses might be better indicators of the LAIV immunogeniticy [61][62][63][64]. As more data becomes available on the antibody responses to different epitopes on the hemagglutinin and other proteins of influenza it may be possible to develop strategies that focus on the generation of responses to conserved eptiopes such as those on the stem of hemagglutinin and thus generate a universal influenza vaccine which avoids problems associated with strain variation [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…LAIV strains developed at the IEM and based on seasonal [20] , pandemic [21] or viruses with pandemic potential [22] were shown to be able to stimulate CD4 + and CD8 + T cells. The same observation is presented here for H7N3 LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity assays, such as hemagglutination inhibition assay, which measure systemic antibody response is inadequate to assess the protective immunity from LAIV: a recent paper showed that LAIV enhanced mucosal IgA avidity (specific local antibodies) in the absence of reliable increases in serum antibody titres. In that study, up to 40% of subjects demonstrated a significant increase in total and virus-specific CD4 memory T cells regardless of immunogenicity results [12]. Immunogenicity of LAIV should thus be evaluated at the mucosal level.…”
Section: Live-attenuated Influenza Vaccine (Laiv)mentioning
confidence: 80%